Syaikh Nawawi al-Bantani’s Perspective on Integrating Sufism and Fiqh to Address Modern Human Challenges - Ihsan, Nur Hadi; Huringin, Nabila; Indah, Nurmala (KARSA Journal of Social and Islamic Culture, 2024)
This research seeks to explore the relationship between Sufism and Fiqh from the perspective of Shaykh Nawawi al-Bantani and its relevance to dealing with various problems and challenges modern human life faces. The problem of spiritual and social crises facing modern humans today arises due to the development of science and technology in the era of globalization, which affects all of their patterns of thinking, acting, and decision-making. This study is qualitative library research. The primary data refers to the work of Shaikh Nawawi al-Bantani, which directly discusses the issues in this work, namely the book Maraqi al-'Ubudiyah and Salalim al-Fudlala'. At the same time, secondary data were taken from various other works of his or the work of other writers and intellectuals. Data was collected using documentary techniques, and the data collected were analyzed utilizing descriptive analysis methods. This study found that Islam consists of three central doctrines: Islam, Iman, and Ihsan. These three doctrines are closely related to the relationship between Sufism and Fiqh, the core of Islamic teachings. If properly understood and realized, the relationship between these two disciplines can play an essential role in helping modern humans overcome the various problems and challenges they face in the spiritual and social crises they experience.